Exploring Innovation Barriers within Local Communities: Toward Sustainable Local Human Resource Development - Suryani, Adi; Suarmini, Ni Wayan; Soedarso; Nisa, Khairun; Saifulloh, Moh. (Journal of Development Research, 2026)
An alternate strategy to improve the standard of living in a community is innovation. A community that is creative or innovative can manufacture products or develop unique ways to do so. The abundance of local resources can serve as a source of inspiration and possible resources to help them support their local innovation. The local community may encounter obstacles even with its wealth of resources. The Community of Sontoh is one of those local communities. Sontoh is blessed with a mangrove habitat and stunning maritime landscape. Sontoh offers marine-based, natural tourism. It also becomes research site. This study intends to investigate the innovation that the Sontoh community faces. The novelty of this study is reflected in its investigation of the multidimensional challenges that constrain local communities from independently developing collective innovation. The study uses qualitative techniques. Direct participant observation is used to collect the data. The community of Sontoh, particularly the women who participate in the study, operate home-based businesses to boost their family's income. They make a variety of local foods, including tahu krispi, kerupuk, otak-otak, pentol ikan, and opak. The two primary obstacles mentioned by the female participants are financial and ICT difficulties. A number of potential supporting factors that can encourage the growth of local innovation are suggested by the study. Information and technology, education, financial inclusion, literacy, community social capital, and organisational building capability are some of these.